Human papillomavirus vaccine uptake and associated factors among adolescent girls in high schools of Nekemte city, Western Ethiopia, 2020 - Genet Hailu; Desalegn Wirtu; Tariku Tesfaye; Motuma Getachew (BMC, 2023)
Abstract Background Cervical cancer is the leading cause of cancer death in adult women in the developing world including Ethiopia. To combat cervical cancer, the World Health Organization (WHO) recommends that girls aged 9-14 years have to take the human papillomavirus vaccine. However, there is a lack of information regarding the uptake of human papillomavirus vaccine in the study area. Therefore, this study aimed to assess the Human Papilloma Virus vaccine uptake and associated factors among adolescent girls in high schools of Nekemte City, Western Ethiopia, 2020. Methods A cross-sectional study design was employed among adolescent girls attending grade 9 and age 15 enrolled at schools in Nekemte City from July 15-30, 2020. Six hundred twenty-six (626) randomly selected adolescent girls were interviewed. The data were entered into Epi Info 7 and analyzed by SPSS 25. Multivariable analysis was computed and a P-value < 0.05 was taken as a cut-off point to declare the statistically significant association. Result The uptake of the HPV vaccine was 61.2%, 95%CI (57.2%, 65%). The Place where adolescents grow up (AOR = 3.46, 95%CI [1.95,6.15]), having a mobile phone(AOR = 1.71, 95%CI [1.05, 2.79]), ever heard about HPV (AOR = 5.69, 95%CI [1.33, 24.27]), ever heard about HPV vaccine(AOR = 1.917, 95%CI [1.002, 3.667]), Ever had sexual intercourse (AOR = 3.04, 95% [1.49,6.20]) and Perceived risk of towards HPV(AOR = 4.63 [2.49, 8.63]) has shown statistically significant association with Uptake of the HPV vaccine. Conclusion Nearly two-thirds of the study participants had taken at least one dose of the HPV vaccine. It is better if health information on HPV is disseminated considering the available technology like mobile phones and reaching rural girls.